2017
DOI: 10.1016/j.vetpar.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analyses of Chinese isolates of Toxoplasma gondii reveal a new genotype with high virulence to murine hosts

Abstract: A great deal of evidence demonstrates that a strongly clonal population structure of Toxoplasma gondii strains exists in humans and animals in North America and Europe, while the strains from South America are genetically separate and more diverse. Potential differences in virulence between different strains mean that an understanding of strain diversity is important to human and animal health. However, to date, only one predominant genotype, ToxoDB#9 (Chinese I), and a few other genotypes, including ToxoDB#20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…However, fine-scale genotyping is imperative to reach definitive conclusions, facilitating the evaluation of the virulence of cat T. gondii strains, and their relationships with ocular toxoplasmosis strains. The clades found with recent phylogenetic analyses based on a concatenated matrix that included the ROP18 gene [15,33,34]. In conclusion, this study confirmed a lack of microscopic detection of oocysts in domestic cats in Armenia (Colombia), but that it is possible to detect and analyze genetic diversity by PCR analysis.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, fine-scale genotyping is imperative to reach definitive conclusions, facilitating the evaluation of the virulence of cat T. gondii strains, and their relationships with ocular toxoplasmosis strains. The clades found with recent phylogenetic analyses based on a concatenated matrix that included the ROP18 gene [15,33,34]. In conclusion, this study confirmed a lack of microscopic detection of oocysts in domestic cats in Armenia (Colombia), but that it is possible to detect and analyze genetic diversity by PCR analysis.…”
Section: Discussionsupporting
confidence: 79%
“…Alignment was performed with MAFFT v7.187 [21], using the auto routine and default settings. Most of downloaded sequences corresponded to the complete gene (1663-1671 bp), depending on the strain [15], and sequences obtained here represented only a partial region. Therefore, we decided not to trim the resulting alignment, as regions dominated by gaps, insertions or deletions usually contain phylogenetically useful information, and the percentage of identity obtained in BLAST suggested that our sequences were sufficiently informative.…”
Section: Discussionmentioning
confidence: 94%
“…However, using this typing method, TgCtwh3 and TgCtwh6 were still grouped together, although they display different phenotypes. As the authors of this work implied, perhaps genotyping using neutral genetic markers is not very useful in predicting pathogenic phenotypes (Gao et al, 2017 ). Therefore, further studies are required to dissect the underlying molecular mechanisms for such phenotypic differences, as a way to better understand the biology of ToxoDB #9 strains.…”
Section: Molecular Basis For Pathogenesismentioning
confidence: 99%
“…However, unlike the clonal nature of the type I, II, and III strains in north America and Europe, there are probably multiple subtypes in the ToxoDB #9 group, since different ToxoDB #9 isolates have quite different properties (such as, acute virulence in mice). Using multilocus sequence typing, a most recent study suggested that ToxoDB #9 isolates could be divided into at least two (potentially more) groups: Chinese I and Chinese III, with Chinese III being more closely related to classic type 1 strains (Gao et al, 2017 ). In addition, the dominating ToxoDB #9 strains seem to be distinct from the strains isolated from other parts of the world.…”
Section: Genotypes Of T Gondii Strains Circulatinmentioning
confidence: 99%
“…The number of T. gondii isolates from China is relatively small in terms of the broad land of the country. It may be related to the China predominant genotype ToxoDB#9, the virulence and cyst-forming capability differ in the strains sharing the same genotype ( Li et al, 2014 ; Gao et al, 2017 ). Furthermore, commercial breeding of experimental animal cats and γ-IFN knockout mice in China is limited.…”
Section: The Molecular Epidemiology Of T Gondii Imentioning
confidence: 99%